Assignment of human beta-, gamma-, and delta-globin genes to the short arm of chromosome 11 by chromosome sorting and DNA restriction enzyme analysis. - Lebo, R V (1979)
Normal human metaphase chromosomes isolated from fibroblasts were resolved into 14 peaks based on total Hoechst 33258 fluorescence and sorted with the fluorescence-activated cell sorter. The chromosomal DNA was extracted and characterized by EcoRI analysis. As expected, analysis of the peak containing chromosomes 16 and 18 detected the alpha-globin genes and of the peak containing chromosomes 9, 10, 11, and 12 detected the beta-, gamma-, and delta-globin genes. Translocations were then used to localize further the beta-, gamma-, and delta-globin genes. The first translocation t(11;22)(q25;q11), which moved nearly all of chromosome 11 to a different peak, confirmed that the beta-, gamma-, and delta-globin genes are on this chromosome. The second, t(4;11)(q25;q13), which moved the distal portion of the long arm of chromosome 11 to a new peak, showed that the genes are not in this segment. The third, t(X;11)(q11;p13), moved the distal region of the short arm of chromosome 11 to a peak which now contained the beta-, gamma-, and delta-globin genes. Therefore, the beta-, gamma-, and delta-globin genes residue on the distal portion of the chromosome 11 short arm including bands p13, p14, and p15. This sorting method may be used generally to assign other genes to chromosomal segments of the entire chromosome complement.